DAMPAK PERCERAIAN ORANG TUA BAGI PSIKOLOGIS ANAK - Sukmawati, Berlia; Oktora, Nency Dela (Center of Gender Studies and Child of State Islamic Institute of Metro, 2021)
The purpose of this study was to determine the impact of parental divorce on children's psychology. The method used is qualitative research with a case study approach. The subjects in this study amounted to one 8-year-old child who resides in Lampung, Metro Regency, North Metro District, 28 Purwoasri using purposive sampling technique, namely sampling where the researcher has determined the criteria for the research subject. The results of this study indicate that divorced parents will have a psychological effect on children, including children who receive less attention, protection, and affection from their father and mother.